(untitled) (Indonesian Minority Justice Review, 2024)
This paper explores the critical role of the Indonesian judiciary in protecting the rights of minority groups through landmark rulings. Despite constitutional guarantees of equality, ethnic, religious, and sexual minorities in Indonesia often face discrimination and exclusion in various spheres of life. The study examines a selection of pivotal court cases in which the Indonesian courts addressed minority rights issues, focusing on decisions related to religious freedom, ethnic discrimination, and gender equality. Through a detailed review of landmark rulings, such as the 2010 judicial review of the Law on Religious Harmony and the 2017 case concerning the rights of transgender individuals, the paper evaluates the effectiveness of the judicial system in upholding constitutional and human rights guarantees. The findings reveal a mixed record: while some cases demonstrate the courts’ commitment to protecting minority rights, others show a reluctance to challenge discriminatory practices, often influenced by political, social, or religious pressures. The paper concludes by recommending reforms to enhance judicial independence, strengthen minority rights protections, and ensure that the courts can more effectively serve as a safeguard against discrimination and marginalization.